International cooperation for enhancing nuclear safety, security, safeguards and non-proliferation -- 60 Years of IAEA and EURATOM : proceedings of the XX Edoardo Amaldi Conference, Accademia Nazionale dei Lincei, Rome, Italy, October 9-10, 2017 /: proceedings of the XX Edoardo Amaldi Conference, Accademia Nazionale dei Lincei, Rome, Italy, October 9-10, 2017. (2018) - Unknown
No abstract available